On local compactness of spaces of continuous valuations - Goubault-Larrecq, Jean (Topology Proceedings, 2024)
We show that the spaces of continuous valuations, resp. subprobability valuations on a locally compact space is locally compact; similarly with probability valuations on locally compact, compact spaces. Continuous valuations are close cousins of measures. No separation property is assumed.